The Application of 3D Virtual Technology in the Teaching of Clinical Medicine. (29th September 2022) - Zhang, Haifeng; Kong, Juan; Tong, Yan; Gao, Chunmei; Huang, Wei
Abstract : The booming development of 3D virtual technology provides the basis for the innovation of teaching mode of clinical medicine. Integrating 3D virtual technology into the clinical education teaching of medical students can help medical students learn clinical expertise more intuitively, enrich practical experience, improve hands-on ability, and make up for the shortcomings of traditional medical teaching. However, the traditional 3D modeling method has the problems of sparse and insufficient accuracy of output results, which greatly limits the specific application of 3D virtual technology in clinical teaching. Therefore, this paper addresses the shortcomings of previous 3D virtual technology in 3D modeling of organs, introduces deep learning, and then proposes a pyramidal shape perception network with the ability to generate samples on point clouds. Experimental results show that the proposed model not only has a large improvement in accuracy but also shows a high degree of confidence in providing real-time feedback of local image attributes.